The effects of penicillin-streptomycin on liver aminotransferases, alkaline phosphatase and total serum protein in rabbits (Orcytolagus coniculus) - T. Akande, S. T. Balogun, O. Gabriel (Journal of Applied Pharmaceutical Science)
The effects of penicillin-streptomycin on some liver enzymes and total serum protein were investigated using thirty adult rabbits (Orcytolagus coniculus) weighing 1.8 – 2.5kg. They were divided into six groups (Groups A – F) of five animals each. Groups A – C received high, moderate and low doses of penicillin-streptomycin, respectively; Group D received penicillin at 10mg/kg twice daily, Group E received streptomycin at 50mg/kg once daily while Group F received normal saline throughout the period of drug administration. All treatments were administered intramuscularly and lasted for ten consecutive days. Serum samples were taken before drug administration (0 hour) to establish baseline parameters and then at 24 and 168 hours post administration of the last dose of the drugs, that is, 11th and 17th days post commencement of treatment. Aspartate amino transferase (AST), alanine amino transferase (ALT), alkaline phosphatse (ALP) and total serum protein were determined in all the serum samples using appropriate methods. The results showed significant increase in AST and ALT when compared with baseline parameters (p < 0.05). In contrast, there was significant decrease in total serum protein (p < 0.05). However, no significant difference was observed in ALP activities before and after drug administration. In conclusion, penicillin-streptomycin could interfere with liver functions by induction of acute hepatitis especially when given in high dosages.
Keywords: Penicillin-streptomycin, Liver enzymes, Effects.